DEVELOPING TASK BASED APPROACH TEACHING MATERIALS AS ALTERNATIVE TO FACE CHALLENGES AND OPPORTUNITIES IN MULTIDIMENSIONAL ENGLISH LANGUAGE TEACHING IN CHANGING EFL CONTEXT - Elvi Elvi (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Facing multidimensional English language teaching in changing EFL context challenges teachers to prepare their students by facilitating them with teaching materials based on the approach that could possibly answer the challenge. This paper try to explore task based approach teaching material which the writer believes has some qualifications for that challenge. It is based on the concept behind the approach that brings the real world task of the language (the usage of the language in the real situation) into pedagogical task (the usage of language in classroom). By transferring the real usage of the language into the usage in classroom in the form of teaching material, it is hoped that the language learning could prepare the students to use the language as it is used to communicate and do other business in life with multi- languages and cultural people in the next free trade. It is also hoped to be used an alternative for the teachers in preparing their classroom activity.  The writer also present – as an example - teaching material, a hand out, for seven grade students of junior high school designed based on the approach. Finally, this paper is hoped can give contributions in designing teaching material for English language teachers.